Menstruation and Human Rights: Can We Move Beyond Instrumentalization, Tokenism, and Reductionism? - Winkler, Inga T. (Columbia Journal of Gender and Law, 2021)
With the current momentum around menstruation, it is increasingly framed as a human rights issue. We see such language in UN documents and many organizations adopt the framing of human rights. Scholars have argued that “framing the issue as being about the right to safe, healthy and dignified menstruation moves it from being a negative problem to be solved” to “an affirmative principle through which the facts of women and girls’ lives are acknowledged and validated.” This paper seeks to briefly unpack what it means to approach menstruation through the lens of human rights. First, I will discuss the predominant way in which human rights framing is presently used and how it is at risk of instrumentalization, tokenism, and reductionism. However, I will also provide a more optimistic view and discuss what the human rights framework has to offer, building on grassroots perspectives as well as normative arguments.